Randomized phase 3 trial of ropeginterferon alfa-2b versus surveillance after tyrosine kinase inhibitor discontinuation in chronic myeloid leukemia (ENDURE/CML-IX) - Burchert, Andreas; Nicolini, Franck E.; le Coutre, Philipp; Saußele, Susanne; Hochhaus, Andreas; Tuere, Evin; Metzelder, Stephan K.; Pauck, Kim; Garn, Holger; Raifer, Hartmann; Huber, Magdalena; Gattermann, Norbert; et al. (Leukemia, 2026)
Treatment-free remission (TFR) after discontinuation of ABL tyrosine kinase inhibitors (TKIs) is an important therapeutic goal in chronic myeloid leukemia (CML). Interferon-α (IFN) has been suggested to promote durable TFR. The phase 3 ENDURE trial (NCT03117816; EUDRA-CT 2016-001030-94) prospectively tested this hypothesis in patients with stable deep molecular remission after TKI therapy. A total of 203 patients were randomised 1:1 to receive ropeginterferon alfa-2b (ropeg-IFN; 100 µg subcutaneously every two weeks for 15 months, n = 95) or observation alone (n = 108) after TKI discontinuation. The primary endpoint was molecular relapse-free survival (MRFS), defined as time to loss of major molecular response (MMR) or death. At a median follow-up of 36 months, 25-month MRFS was 56% (95% confidence interval (CI), 45-66) with ropeg-IFN and 59% (95% CI, 49-68) with observation (hazard ratio (HR), 1.02; 95% CI, 0.68-1.55; P = 0.91). Among 83 patients with molecular data after TKI restart, 79 (95%) regained at least MMR, 78 within 12 months (median 3 months, interquartile range: 2-4 months). Ropeg-IFN was well tolerated (median administered dose of 92 µg, range 3-104), and no new safety signals were observed. Ropeg-IFN maintenance did not improve the probability of sustained TFR after TKI discontinuation.
Gesehen am 05.02.2026